Academic Fraud Enigma among Accounting Vocational School Students: Insights from Heptagon Framework and Relevance of Artificial Intelligence - Lestari, Sari; Mutmainah, Siti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to investigate the influence of heptagon theory elements, including pressure, opportunity, rationalization, competency, arrogance, greed, and ignorance, on academic fraud. Additionally, the study seeks to assess the moderating effect of Chat GPT usage, an artificial intelligence application, on the relationship between each element of heptagon theory and academic fraud. Employing a quantitative approach, the study focuses on the population of accounting students in vocational high schools, with a sample of 120 respondents meeting representativeness criteria calculated using the Cochran formula. Primary data is collected through respondents' responses obtained via a Google Form questionnaire. The results indicate that rationalization, competency, and greed exert has a significant influence on academic fraud among accounting students, whereas pressure, opportunity, arrogance, and ignorance do not exhibit a significant impact. Chat GPT, representing artificial intelligence, does not moderate the relationship between heptagon theory elements and academic fraud.